KEEFEKTIFAN DOSIS KOAGULAN POLY ALUMINIUM CHLORIDE(PAC) DALAM MENURUNKAN KADAR CHEMICAL OXYGEN DEMAND (COD) PADA AIR LIMBAH LAUNDRY - Harwiyanti, Retno Dwi, Heru Subaris Kasjono, SKM., M.Kes, Dwi Astuti, SKM., M.Kes (2015)
Chemical Oxygen Demand (COD) is one of the parameters contained in the laundry waste water. The higher levels of COD in water indicates that the water pollution is also higher. Waste water measurement results Pratama Laundry indicate COD concentration of 385.92 mg/l. This value exceeds the quality standards established. The purpose of this study was to determine the dose of PAC coagulant addition most effective way to reduce levels of COD in waste water facilities. This research was experiment with a pretest-posttest design with control group. The population in this study is the wastewater generated from the process of laundering activities Pratama Laundry produce waste water output of 200-210 liters/day and the sampling technique using a quota sampling. Statistical test using ANOVA test with the results of the analysis of data obtained p = 0.000 (p <0.01),Hareceivedmeansthatthere isthe effect of addinga coagulantPACin lowering levels ofCODinlaundry waste water. Obtainedthe highestdeclineof71.79% (108.87 mg/l) at a doseof 0.75g/l.